Is locking compression plate the best modality of treatment for distal femur fractures? - Koteeswar Rao, R. G.; Mohanraj, Pratheesh; M., Mohan Kumar (International Journal of Research in Orthopaedics, 2018)
Background: This observational study was conducted in order to study the functional efficacy of locking compression plate in distal femur fractures as they are one of the most common type of fractures with bimodal age distribution affecting younger age group as a consequence of high energy trauma especially road traffic accidents and elderly population due to osteoporosis. Methods: 40 Patients who are skeletally matured with acute distal femur fractures were radiologically assessed type of fractures, amount of comminution, articular congruence and quality of bone. pretested proforma which include age, sex, occupation, mode of injury, type of fracture, time interval between injury and surgery, associated comorbid conditions and other associated injuries. Results: Off the 40 patients under study 21 showed excellent outcome according to neers rating system and only 5 had fair results, 3 patients had superficial wound infection and 5 developed knee stiffness. Conclusions: Locking compression plate produces better results and appears to be good method of management in distal femur fractures.